Integration Bioprocess of B-Phycoerythrin and Exopolysaccharides Production From Photosynthetic Microalga Porphyridium cruentum - Yin, Hao-Chan; Sui, Ji-Kang; Han, Tian-Li; Liu, Tian-Zhong; Wang, Hui (Frontiers in Marine Science, 2022)
Red microalga Porphyridium cruentum has great potential for converting CO2 to high-value bioactive compounds exopolysaccharides (EPS) and B-phycoerythrin (B-PE), The present study aims to establish the integration bioprocess of EPS and B-PE production from P. cruentum. Firstly, different kinds of growth medium and CO2 concentration were assessed indoor in terms of high biomass and EPS and B-PE contents. As follows, P. cruentum cells were outdoor scale-up cultured in 700L pressurized tubular reactors for 9 days till the biomass reached 0.85g L-1, and then separated from supernatants via centrifugation. Three different methods were adopted to extract phycobiliproteins, and the highest PE contents extracted from cells by repeated freeze-thawing treatment along with the optimization of significant variables, and finally, 7.99 mg L-1 B-PE (16500Da) with a purity index of 0.82 was obtained. Moreover, analysis of physicochemical properties of EPS extracted from P. cruentum showed that the sulfate content was 14.85% and uronic acid content was 9.36%.